ChemInform Abstract: Asymmetric Synthesis of Spiropyrazolones Through Phosphine‐Catalyzed [4 + 1] Annulation. Issue 46 (18th November 2014) - Han, Xiaoyu; Yao, Weijun; Wang, Tianli; Tan, Yong Ren; Yan, Ziyu; Kwiatkowski, Jacek; Lu, Yixin
Abstract The title synthesis represents the first asymmetric application of α‐substituted allenoates in [4 + 1] annulation.